2015
DOI: 10.1128/jcm.02473-14
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Multiple-Locus Variable-Number Tandem-Repeat Typing Scheme for Genetic Fingerprinting of Burkholderia cenocepacia and Application to Nationwide Epidemiological Analysis

Abstract: Organisms of the Burkholderia cepacia complex are especially important pathogens in cystic fibrosis (CF), with a propensity for patient-to-patient spread and long-term respiratory colonization. B. cenocepacia and Burkholderia multivorans account for the majority of infections in CF, and major epidemic clones have been recognized throughout the world. The aim of the present study was to develop and evaluate a multilocus variable-number tandem-repeat (VNTR) analysis (MLVA) scheme for B. cenocepacia. Potential VN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
(30 reference statements)
1
4
0
Order By: Relevance
“…Interestingly, the isolates originated from various sources and were isolated at different times: river, hospital sink (2012) and 3 CF patients (2008,2010). These discrepancies were already described for P. aeruginosa or Burkholderia cepacia complex [27,28]. Nevertheless our results are discordant with those of Barrado et al who noticed that "in all cases in which a common ST was found, the PFGE patterns were also indistinguishable" [13].…”
Section: Discussionsupporting
confidence: 72%
“…Interestingly, the isolates originated from various sources and were isolated at different times: river, hospital sink (2012) and 3 CF patients (2008,2010). These discrepancies were already described for P. aeruginosa or Burkholderia cepacia complex [27,28]. Nevertheless our results are discordant with those of Barrado et al who noticed that "in all cases in which a common ST was found, the PFGE patterns were also indistinguishable" [13].…”
Section: Discussionsupporting
confidence: 72%
“…For the above reasons, alternative methods were developed to allow routine or large-scale analysis, such as the SNaPBcen assay targeting only single nucleotide polymorphisms in MLST genes instead of analyzing full sequences ( Eusebio et al, 2013 ); the PCR assays based on MLST and specific for particularly globally distributed epidemic strain ( Dedeckova et al, 2013 ); or multilocus variable-number tandem-repeat analysis (MLVA) ( Segonds et al, 2015 ).…”
Section: Epidemiology Of B Cenocepacia Strainsmentioning
confidence: 99%
“…The Burkholderia cepacia complex (Bcc) includes at least 18 species of aerobic, Gram‐negative rods that are ubiquitous in the environment but can cause opportunistic infections . Burkholderia multivorans and B. cenocepacia are most often associated with Bcc infections in humans, particularly cystic fibrosis patients .…”
Section: Introductionmentioning
confidence: 99%